Tingkat Kekerasan Dan Daya Terima Tempe Goreng Dari Kedelai Lokal Dan Impor - Muslihah, Jami'atul, Rusdin Rauf, S.TP., M.P, Eni Purwani, S.Si., M.Si (2014)
Background: Tempe has a high potential to be develop because Tempe as a cheap vegetable protein source and nutrition content for health. The purpose of this research is for increase variety of local Tempe that become a proceed product that panelists like. Method: research of method for this research is experiment research. Research plan that used is a complete random plan with three times repeat. The data of rough level and acceptance capacity use t-test independence statistic test. Result: test result t is rough significant value p=0,063v (p >0, 05) that means there is no different of local soy-bean fried Tempe and import soy bean fried Tempe in rough level. Whereas the result of test is 56% panelists' dislikes color of local soy-beans fried Tempe and 76% panelist rather like. Thus there is a difference in fried Tempe color acceptance. The test result percentage acceptance capacity of local fried Tempe fragrance show that 52% panelists dislike the color of local soy-bean fried Tempe and 76% is like the color of import soy-bean fried Tempe. Thus there is a difference in fried Tempe fragrance acceptance. The result percentage of acceptance capacity flavor of fried Tempe show that 48% panelists very dislike the flavor of local soy-beans fried Tempe and 56% panelists like the flavor of import soy-beans fried Tempe. Thus there is a difference in fried Tempe flavor acceptance. The result percentage of acceptance capacity in texture of fried Tempe show that 68% like the texture of local soy-beans friend Tempe and 64% like the texture of import soy beans friend Tempe. Thus there is no difference in acceptance capacity in texture of fried Tempe. The result percentage acceptance capacity overall show that 48% panelists dislike local soy bean fried Tempe and 72% like import soy bean fried Tempe. Thus there is a difference in acceptance capacity in fried Tempe. Conclusion: the conclusion of this research is there is no difference in rough level and acceptance capacity in local soy bean and import soy bean fried Tempe's texture. There is a different in color acceptance, fragrance acceptance, flavor acceptance, and overall of fried Tempe that made of local soy bean and import soy bean.